(untitled) (Physical Education, Health and Social Sciences, 2025)
This paper explores the interactive association between information and communication technology (ICT), financial development, use of renewable energy, and carbon dioxide (CO2) emissions in selected South Asian countries from 2004-2024. The analysis includes second-generation panel econometric methods, such as CIPS and CADF unit root tests, Pedroni residual cointegration tests, and panel ARDL-PMG estimator, based on panel data of the World Development Indicators (WDI) to explain cross-sectional dependence and heterogeneity among countries. The Pedroni cointegration findings support the existence of a stable relationship between CO2 emissions and ICT in the long run and consumption of renewable energy but the association with the financial development and GDP is quite low. The estimates of the long-run PMG show that the consumption of renewable energy lessens the emissions of CO2 greatly underlining the importance of the latter in the sphere of environmental mitigation, but the ICT development shows a positive impact on the emissions, which means that digital growth in the area is power-consuming and can provoke backlash. The fact that the error-correction term is insignificant implies that there is a slow-adjustment to the long-run equilibrium, i.e. a delay in policy transmission mechanisms. These findings underscore the need to have a combined policy measures to ensure the adoption of renewable energy, orient ICT infrastructure towards low-carbon development as well as harmonize financial development with green investments. The research will give practical insights to policymakers to come up with holistic energy, technology and financial policies to cut down carbon emissions and ensure that the South Asian region has sustainable economic growth.